Enhancing Maritime Vocational Education : Integrating Sustainability, Employability, and Career Pathways - Boedojo Wiwoho Soetatmoko Jogo; Rosmayana Rosmayana (Institut Nalanda, 2025)
The maritime industry faces increasing pressure to adapt to sustainability goals and provide skilled professionals capable of navigating environmental and technological changes. This research investigates the integration of sustainability into maritime vocational education, its impact on employability, and the development of clear career pathways for graduates. The study aims to answer key questions about how sustainability is incorporated into curricula, how employability skills are developed, and how career pathways are structured for maritime students. A qualitative approach, including interviews with 10 maritime professionals, lecturers, and graduates, along with a systematic literature review (SLR), was employed to explore these issues. The results highlight that while technical skills are well-developed in maritime education, there is a significant gap in soft skills development, such as communication and leadership. Additionally, career pathways and industry-academia collaborations were found to be underdeveloped, hindering graduates' transitions into the workforce. The findings emphasize the importance of a more standardized approach to sustainability in maritime education, enhanced soft skills training, and stronger industry connections to support students' career progression. This research contributes to the growing body of literature on maritime education, offering practical implications for enhancing curricula, improving employability, and creating clearer career pathways in maritime vocational training.